2021
DOI: 10.1096/fj.202100107r
|View full text |Cite
|
Sign up to set email alerts
|

Avian red blood cell mitochondria produce more heat in winter than in autumn

Abstract: Endothermic animals that reside year-round in the temperate zone must accommodate pronounced seasonal changes to ambient temperature, photoperiod, precipitation, and food availability. The stresses imposed by these environmental factors intensify in winter, when low ambient temperature increases the energy cost of staying warm at the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
45
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(54 citation statements)
references
References 50 publications
6
45
3
Order By: Relevance
“…Prenatal exposure to heat-calls induced a shift of nestling mitochondrial function towards higher ATP production ( OXPHOS ) and therefore lower FCR L/R and FCR L/ETS under undisturbed in-nest conditions. The prenatal acoustic signal, therefore, had similar impact on mitochondria to that of direct exposure to environmental temperatures in other species [ 26 , 28 , 31 ]. For example, in adults of three tit species, acclimatization to low winter temperatures increased LEAK respiration in RBCs [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prenatal exposure to heat-calls induced a shift of nestling mitochondrial function towards higher ATP production ( OXPHOS ) and therefore lower FCR L/R and FCR L/ETS under undisturbed in-nest conditions. The prenatal acoustic signal, therefore, had similar impact on mitochondria to that of direct exposure to environmental temperatures in other species [ 26 , 28 , 31 ]. For example, in adults of three tit species, acclimatization to low winter temperatures increased LEAK respiration in RBCs [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…LEAK can also reduce the oxidative damage associated with the production of reactive oxygen species (ROS) in mitochondria (‘uncoupling to survive hypothesis' [ 35 ]). This leads to trade-offs between energy production, heat generation and oxidative balance [ 36 ], with LEAK accounting for 20–70% of cellular respiration, or up to 25% of the organismal basal metabolic rate [ 28 , 34 , 37 ]. LEAK proportion and therefore mitochondrial efficiency (inverse to the ratio of LEAK over mitochondrial overall respiration under endogenous ( ROUTINE ) or stimulated ( ETS ) conditions) can differ between species [ 12 ], but also between individuals [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though blood volume represents ∼8-10% of the total volume in birds (Sturkie and Griminger, 1986), it is unknown what proportional contribution blood cells make to the total metabolic rate. Nord et al (2021) reported that coal tits (Periparus ater) and great tits (Parus major) increased their mitochondrial respiration rates and CS activity of RBCs in winter, which may be a response to changes in metabolic demands between seasons. In the following sections, we offer alternative explanations for the observed increases in mass-adjusted BMR and COX activity in RBCs and why it could be associated to the costs of osmotic stress.…”
Section: Energy and Osmoregulatory Adjustmentsmentioning
confidence: 99%
“…One of the unique characteristics of birds and often overlooked by ecological and evolutionary physiologists is the presence of nucleated RBCs with functional mitochondria. This key feature has recently caught the attention of physiologists and the existence of intra and interspecific variation in its function has been observed in a few species (Stier et al, 2013(Stier et al, , 2015(Stier et al, , 2017Nord et al, 2021). Decades ago, some suggested that ATP production in erythrocytes is involved in the maintenance of ion balance (Na and K) between erythrocytes and plasma (Hunter and Hunter, 1957).…”
Section: Changes In Erythrocyte Metabolic Activitymentioning
confidence: 99%